A Real-Time Spine Orthopedic System Based on Bluetooth Low Energy and Internet of Things - Kun Xia; Ruifeng Hou; Junlin Yang; Xiang Li (IEEE Access)
A real-time spine orthopedic system based on Bluetooth Low Energy (BLE) and Internet of Things (IoT) is proposed in this paper. The proposed system could realize the networking communication based on BLE, and upload the device data onto the cloud server via a 4G/5G communication network. IoT integrated with cloud servers and terminal applications allows the real-time monitoring process of spinal orthopedics. The digital linear actuator in the device can stretch through program control, in order to realize the accurate control of spinal orthopedic process. Then, the user could query and store the running information about the device through the personal computer-side web or mobile phone with remote control. In addition, the multi-device database is built on the cloud server, which is conducive to the further analysis and processing of spinal orthopedic data. This article presents the hardware design of spinal orthopedic device, builds the user software at the application layer, and forms the multi-device database through the cloud server. The final experimental results show that the proposed system can realize the function of spinal orthopedic and upload the device data in real-time.